2015
DOI: 10.3852/13-380
|View full text |Cite
|
Sign up to set email alerts
|

MultiplePhytophthoraspecies associated with a single riparian ecosystem in South Africa

Abstract: The diversity of Phytophthora spp. in rivers and riparian ecosystems has received considerable international attention, although little such research has been conducted in South Africa. This study determined the diversity of Phytophthora spp. within a single river in Gauteng province of South Africa. Samples were collected over 1 y including biweekly river baiting with Rhododendron indicum leaves. Phytophthora isolates were identified with phylogenetic analyses of sequences for the internal transcribed spacer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…In accord with previous studies in other areas of the world [38,39,41,50], Clade 6 species prevailed in rivers, indicating their adaptation to aquatic environments. Interestingly, two mainly aquatic opportunistic pathogens from Clade 6, P. gonapodyides and P. lacustris, which often co-occur in river systems in temperate regions of North America, Europe, and Asia [40,[77][78][79], showed opposite distribution patterns in Sicily.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accord with previous studies in other areas of the world [38,39,41,50], Clade 6 species prevailed in rivers, indicating their adaptation to aquatic environments. Interestingly, two mainly aquatic opportunistic pathogens from Clade 6, P. gonapodyides and P. lacustris, which often co-occur in river systems in temperate regions of North America, Europe, and Asia [40,[77][78][79], showed opposite distribution patterns in Sicily.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, great attention has been paid to surface water as a source of Phytophthora inoculum in natural ecosystems. Surveys of rivers, streams, and riparian ecosystems in several continents have revealed a huge diversity of Phytophthora species, including primarily aquatic species which are considered as opportunistic pathogens, but also soilborne and airborne primary pathogens [8,20,21,[37][38][39][40][41]. However, all Phytophthora species have the potential to be disturbance factors in natural ecosystems, in particular, those of exotic origin, provided that the environmental conditions are conducive to disease development [9,10,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption is now being cast in doubt due to the widespread identification of Phytophthora spp. in streams and forests from across the globe (6)(7)(8)(9)(10)(11)(12)(13). Currently, these species are hypothesized to be waterborne opportunistic pathogens, foliar pathogens, and fine-root or canker pathogens (14).…”
mentioning
confidence: 99%
“…reside in the the same Order as asparagus (Asparagales). In contrast, finding P. amnicola was not surprising because three previous studies have identified hybrid progeny indicating that it is common n Sout African rivers (Nagel et al 2013(Nagel et al , 2015Oh et al 2013).…”
Section: Discussionmentioning
confidence: 93%